Introduction: exploring Cora Diamond's significances for education and educators. Issue 1 (2nd January 2021) - Frank, Jeff; Laverty, Megan
ABSTRACT: This paper introduces the special section on Cora Diamond's significance for education and educators. The introduction is meant to be the beginning of a conversation, and—to that end—the special section editors suggest lines of connections that philosophers of education might draw between their work and the work of Cora Diamond. Their list is not meant to be exhaustive, but it is meant to suggest Diamond's far-reaching significance for education and educators.